If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30 = -2(-1n + 3) Reorder the terms: -30 = -2(3 + -1n) -30 = (3 * -2 + -1n * -2) -30 = (-6 + 2n) Solving -30 = -6 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -30 + -2n = -6 + 2n + -2n Combine like terms: 2n + -2n = 0 -30 + -2n = -6 + 0 -30 + -2n = -6 Add '30' to each side of the equation. -30 + 30 + -2n = -6 + 30 Combine like terms: -30 + 30 = 0 0 + -2n = -6 + 30 -2n = -6 + 30 Combine like terms: -6 + 30 = 24 -2n = 24 Divide each side by '-2'. n = -12 Simplifying n = -12
| P^3+4p^2+8p+32=0 | | 9y=7y+8 | | -y-2(2y-1)=5(1-y) | | 8=10-2n | | 3x^2-5=54 | | 8=10-2 | | 8x-9y+73= | | 4(x-1)-x=23 | | Y=-2x^2+4x+8 | | x+3.5x=9.90 | | -6k-7=-(6k-7) | | 10=6+2w | | 30x^3-24x^2-15x+12=0 | | 2x-84=7x-4 | | 8(p-3)=8(1+p) | | 3g-5=1 | | x-14+2x=16 | | (2y-1)(y-2)=6 | | 9x+84=12 | | 5y+13=2y+22 | | 6x-4-4x=2x-4 | | 4x+15=24 | | 24-64n=-8(-3+8n) | | 7x-13=42 | | 4x^2-17x-15=30 | | -85=5(2n-3) | | 3x+10=2x-x+18 | | 11x+25=78 | | -2(z-3)-4=18 | | -2-(12x+8)+17=3+x-(13x-4) | | -12z-29=5(z+6)-195 | | 5(v-8)-2=5v+29 |